Relations between the Centre and Surroundings in the Functional Area of the Poznań Agglomeration - Budner, Waldemar W. (Studia Oeconomica Posnaniensia, 2015)
The paper presents the changes in relationships between the centre (Poznań) and its surrounding area in 2000-2010. The subjects of discussion are the demographic relationships (structural quantitative, including migrations). The background of the analysis is employment and the dominant features of the agglomeration. The boundaries of the functioning agglomeration were set on the basis of the ratio of commuters and employees (according to The Urban Audit).